m6A methylation: Critical roles in aging and neurological diseases - Fan, Yishu; Lv, Xinyi; Chen, Zhuohui; Peng, Yanyi; Zhang, Mengqi (Frontiers in Molecular Neuroscience, 2023)
RNA methylation participates in the functional regulation of various biological processes, affecting RNA translocation, alternative splicing, maturation, stability, and degradation to regulate the expression of targeted genes. Among different methylation modifications, N6-methyladenosine (m6A) is the most abundant internal RNA modification in eukaryotic cells. As recent evidence shows, of all organs, brain has the highest abundance of m6A methylation of RNAs, which indicates its regulating role in central nervous system (CNS) development and the repair and remodeling of the cerebrovascular system. Neurovascular unit (NVU) is a structural and functional unit of brain. It is composed of neurons, blood-brain barrier, microglia, pericyte, astrocyte and surrounding extracellular matrix, etc. Remodeling of NVU have significant influence on the prognosis of various neurological manifestations. However, the relationship between RNA methylation and NVU remodeling, especially under disease conditions, remains unknown. In this manuscript, we focus on m6A methylation associated mechanisms in the remodeling of neurovascular units and summarize their effects in several neurological manifestations, including ischemic stroke, Parkinson's disease (PD), Alzheimer's disease (AD), multiple sclerosis, depression, epilepsy, and gliomas. We hope to provide a new direction for the molecular mechanism and novel therapeutic targets of these diseases.